The pragmatic role of nasal cytology: a point-of-care testing to implement precision medicine in clinical practice - Matteo Gelardi; Massimo Landi; Giorgio Ciprandi (Revista Alergia México, 2018)
Background: Precision medicine is an up-to-date strategy aimed at individualizing precise pathophysiological mechanisms. Thus, precision medicine is the basis for personalized medicine, inasmuch as it seeks to define the most appropriate treatment for each patient. Nasal cytology requires only an optical microscope, stains, glasses, and nasal cytology curettes. The procedure may last very few minutes using quick staining and, therefore, it can be considered a reliable point-of-care test in the office setting.